2000
DOI: 10.1055/s-2000-6864
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Human Immunodeficiency Virus And Acquired Immunodeficiency Syndrome: An Overview

Abstract: This article covers the epidemiological manifestations of human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) in children, demographic statistics, and information on the three modes of virus transmission. The various opportunistic diseases and neurological dysfunction that characterize pediatric HIV are described. The Center for Disease Control pediatric HIV classification system is presented, and the developmental disorders often found in children with HIV are discussed. The Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The proportion of normal audiologic and electrophysiologic test results was significantly higher in the three -six-year-old controls than in those with AIDS (Table 1). Other studies have also demonstrated a higher incidence of auditory disorders in children with AIDS [14][15][16].…”
Section: Occurrence Of Auditory Disorders In Children Ranging From 3 mentioning
confidence: 99%
“…The proportion of normal audiologic and electrophysiologic test results was significantly higher in the three -six-year-old controls than in those with AIDS (Table 1). Other studies have also demonstrated a higher incidence of auditory disorders in children with AIDS [14][15][16].…”
Section: Occurrence Of Auditory Disorders In Children Ranging From 3 mentioning
confidence: 99%